Does multilingualism confer an advantage for pragmatic abilities? - Antoniou, Kyriakos; Grohmann, Kleanthes K.; Kambanaros, Maria; Katsos, Napoleon (My University, 2013)
Experimental evidence suggests that bilingualism leads to an advantage in children’s executive control (EC), Theory of Mind (ToM) and pragmatic abilities (e.g. Bialystok 2009; Goetz 2003; Siegal et al. 2009; 2010). In this study we aimed to investigate (1) whether multilingualism confers an advantage in children’s ability to understand implicatures and (2) whether a potential multilingual advantage in this ability is mediated by some aspect of EC or ToM. In order to achieve these aims we tested multilingual and bilectal children growing up in the Republic of Cyprus where the linguistic situation is typically described as one of diglossia. Children were administered (a) an extensive battery of tasks that cover all aspects of EC (cognitive flexibility, working memory and inhibition) and ToM and (b) a novel and extensive conversational test examining their ability to understand a wide range of implicatures based on Grice’s maxims of conversation. Overall, there was only suggestive evidence for a multilingual advantage in pragmatic language. Our results also revealed a multilingual advantage in inhibitory control skills. Finally, we found no evidence for a positive link between pragmatic ability and cognitive factors such as EC or ToM. We discuss whether the lack of robust evidence in favour of a multilingual advantage in comprehending implicatures could be due to the bilectal status of our control group.
Keywords: Bilingualism; Theory of mind